Goal Setting for Cognitive Rehabilitation in Mild to Moderate Parkinson’s Disease Dementia and Dementia with Lewy Bodies - Tamlyn J. Watermeyer; John V. Hindle; Julie Roberts; Catherine L. Lawrence; Anthony Martyr; Huw Lloyd-Williams; Andrew Brand; Petra Gutting; Zoe Hoare; Rhiannon Tudor Edwards; Linda Clare (Parkinson's Disease)
Alongside the physical symptoms associated with Parkinson’s disease dementia and dementia with Lewy bodies, health services must also address the cognitive impairments that accompany these conditions. There is growing interest in the use of nonpharmacological approaches to managing the consequences of cognitive disorder. Cognitive rehabilitation is a goal-orientated behavioural intervention which aims to enhance functional independence through the use of strategies specific to the individual’s needs and abilities. Fundamental to this therapy is a person’s capacity to set goals for rehabilitation. To date, no studies have assessed goal setting in early-stage Parkinson’s disease dementia or dementia with Lewy bodies. Semistructured interviews were carried out with 29 participants from an ongoing trial of cognitive rehabilitation for people with these conditions. Here, we examined the goal statements provided by these participants using qualitative content analysis, exploring the types and nature of the goals set. Participants’ goals reflected their motivations to learn new skills or improve performance in areas such as technology-use, self-management and orientation, medication management, and social and leisure activities. These results suggest that goal setting is achievable for these participants, provide insight into the everyday cognitive difficulties that they experience, and highlight possible domains as targets for intervention. The trial is registered with ISRCTN16584442 (DOI 10.1186/ISRCTN16584442 13/04/2015).